Strategi Pengembangan Pariwisata Alam di Taman Wisata Alam Gunung Pancar (Jurnal Ilmiah Pariwisata, 2014)
This study was aimed at identifying both influential internal and external strategic factors to find strategy alternatives, and to determine the strategy priorities for the nature tourism development of Pancar Mountain Nature Park. This study used a descriptive method through surveys, and respondents through a purposively chosen involving the experts and stakeholders in the study area, who were assumed to master the problems of Pancar Mountain Nature Park. The analysis of the data was carried out progressively, beginning with the analysis of Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), the matrix of Internal-External (IE), the matrix of SWOT (Strenghts, Weakness, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix). This study finally recommended six strategys in the following order : 1) product development strategy through the development of types tourism attractions, 2) market penetration strategy through increased promotion/marketing of nature tourism with the use of information technology, 3) optimize the cooperation of all stakeholders in managing Pancar mountain nature park, 4) to clarify the broad and bounds of the Pancar mountain nature park areas, 5) strategy to increased society participation in nature tourism cultivation activities, and 6) increase the role of association in the management activity of Pancar mountain nature park.